The Psychological Well-Being of Front-Line Clinical Professionals during Wide Scale Organisational Change: A Qualitative Study of NHS Staff - Seela Bhadran, Renjith (2013)
Although the clinical profession is often regarded as stressful, vulnerable to various types of dangerous situations and psychologically demanding environments, there has been an astonishing lack of study into the area of psychological well-being amongst clinical professionals, especially during a period of organisational change. This research study is rare and a combination of aspects related to the principles of HR, Strategic management, Organisational change, Psychology and Public Health.